Binding of HCN channels to GABAB receptors in dopamine neurons of the VTA limits synaptic inhibition and prevents the development of anxiety - Enrique Pérez-Garci; Kateryna Pysanenko; Giorgio Rizzi; Florian Studer; Daniel Ulrich; Thorsten Fritzius; Simon Früh; Alessandra Porcu; Valérie Besseyrias; Adolf Melichar; Martin Gassmann; Tania Rinaldi Barkat; et al. (Neurobiology of Disease)
During GABAergic synaptic transmission, G protein-coupled GABAB receptors (GBRs) activate K+ channels that prolong the duration of inhibitory postsynaptic potentials (IPSPs). We now show that KCTD16, an auxiliary GBR subunit, anchors hyperpolarization-activated cyclic nucleotide-gated (HCN) channels containing HCN2/HCN3 subunits to GBRs. In dopamine neurons of the VTA (DAVTA neurons), this interaction facilitates activation of HCN channels via hyperpolarization during IPSPs, counteracting the GBR-mediated late phase of these IPSPs. Consequently, disruption of the GBR/HCN complex in KCTD16−/− mice leads to prolonged optogenetic inhibition of DAVTA neuron firing. KCTD16−/− mice exhibit increased anxiety-like behavior in response to stress - a behavior replicated by CRISPR/Cas9-mediated KCTD16 ablation in DAVTA neurons or by intra-VTA infusion of an HCN antagonist in wild-type mice. Our findings support that the retention of HCN channels at GABAergic synapses by GBRs in DAVTA neurons provides a negative feedback mechanism that restricts IPSP duration and mitigates the development of anxiety.